Effect of Additive Ingredients in Papaya Leaf-Based Botanical Pesticides on the Vegetative Growth of Water Spinach (Ipomoea reptans Poir) - Nurul Chairiyah; Ipun; Dwi Santoso; Nur Indah Mansyur; Nurmaisah; Muh Adiwena; Muttaqien (Postgraduate, University of Mataram, 2026)
This study evaluated the effect of additives in papaya leaf–based botanical pesticides on the vegetative growth of water spinach (Ipomoea reptans Poir). The experiment was arranged using a Randomized Complete Block Design (RCBD) with five treatments and five replications: P0 (control), P1 (papaya leaves), P2 (papaya leaves + garlic), P3 (papaya leaves + lemongrass), and P4 (papaya leaves + soursop leaves). Observed parameters included plant height, root length, number of leaves, and fresh weight. Data were analyzed using analysis of variance (ANOVA), Duncan’s Multiple Range Test (DMRT) at 5%, correlation, and multiple linear regression analyses. The treatments significantly affected most growth parameters. P3 (papaya leaves + lemongrass) produced the best performance, with plant height of 24.35 cm, root length of 22.58 cm, approximately 18 leaves, and fresh weight of 14 g. Correlation analysis showed strong positive relationships between plant height and number of leaves (r = 0.890), and between root length and fresh weight (r = 0.764). Regression analysis identified number of leaves as the strongest predictor of fresh weight (β = 1.015), followed by root length (β = 0.528), whereas plant height showed a negative effect (β = −0.891). Overall, the addition of lemongrass to papaya leaf–based botanical pesticides enhanced vegetative growth and biomass accumulation in water spinach plants.